The figures of styles in «the elige of Kairaouan» of Ibn Rachik el-msili: a stylistic study - Asasla, Fouzia (Journal of Human Sciences, 2021)
The figures of styles have had a strong presence in the poem"kamkanfiha min kiraminsadatin",was known as the IbnRachik el-msilielige,so that no verse was disturbed by its existence.What we have been pushed to study,a stylistic study,and what will be in this article,which we will draw the distinctive images of the style of the poem,and its formation in the way they interact to draw the general form of the poem, and its impact on the recipient through the following points:   -The repetition rates of style figures in the elige.   -Demonstrate the construction of style figures whose purpose is to take figures as a means of expression.